2021
DOI: 10.3389/fphys.2021.685664
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Exercise-Training-Related Functional and Morphological Adaptation of Rat Gracilis Muscle Arterioles

Abstract: BackgroundThe cardiovascular effects of training have been widely investigated; however, few studies have addressed sex differences in arteriolar adaptation. In the current study, we examined the adaptation of the gracilis arterioles of male and female rats in response to intensive training.MethodsWistar rats were divided into four groups: male exercise (ME) and female exercise (FE) animals that underwent a 12-week intensive swim-training program (5 days/week, 200 min/day); and male control (MC) and female con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Regarding coronaries, we found that the arteriolar segments contractibility was increased in females and relaxation capacity was increased in males [ 10 ]. Regarding the gracilis arteriole, tangential wall stress and norepinephrine-induced contraction were elevated in female rats compared to in male animals [ 11 ]. During the examination of a visceral large artery (renal artery), we found that phenylephrine-induced vasoconstriction was reduced in males, but not in females [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding coronaries, we found that the arteriolar segments contractibility was increased in females and relaxation capacity was increased in males [ 10 ]. Regarding the gracilis arteriole, tangential wall stress and norepinephrine-induced contraction were elevated in female rats compared to in male animals [ 11 ]. During the examination of a visceral large artery (renal artery), we found that phenylephrine-induced vasoconstriction was reduced in males, but not in females [ 12 ].…”
Section: Introductionmentioning
confidence: 99%